ANALISIS ASPEK FAKTOR LINGKUNGAN FISIK PADA INDUSTRI TAHU DI KELURAHAN JOMBLANG KECAMATAN CANDI SARI KOTA SEMARANG - Ulfa Nurullita (Jurnal Kesehatan Masyarakat Indonesia, 2008)
Background: Tofu industrial was one of kind the informal industrial. In the works of process, the workers will get the work load and additional load was causes &om work areas. One of tofu industrial was in KelurahanJomblang, it controll just go from public health facility wich didn't do routine, it is just observed from disease aspect of generally case appear, was Dermatitis, it didn't reached controlling of by work health and safety up till now. Methode: The total of samples are 42 people. The kind of research was deskriptif. The factors were onserved are lighting intensity (with luxmeter), sound intensity (with sound level meter), heat skess (withquestemp), smell (with sense of smell), ventilation (with meter), complaint about the comfortable production room and sickness complaint from employee (with questioner). Result: lighting intensity range 78,6 lux (2 locations more over minimum), sound intensity range 95,7 dBA (all of industries more over limit value), heat stress range 42,4"C(all ol industries over limit value), humadity range 43,8Yo (all of them under the limit value), the broad ventilation range 29,4o/o from the floorspace (3 locations which do not fulfill condition), the complaint about less complexion intensity are 8 people (19W, about sound intensity (noise) are 39 people (92,9yo), about heat stress are 38 people (90,5yo), the majority of disease complaint about 17 people (40,5o/o) was kutu air.